Bachelor Japanists : Japanese aesthetics and Western masculinities - Reed, Christopher, 1961- (Modernist latitudes., 2017)
Challenging clichés of Japanism as a feminine taste, 'Bachelor Japanists' argues that Japanese aesthetics were central to contests over the meanings of masculinity in the West. Christopher Reed draws attention to the queerness of Japanist communities of writers, collectors, curators, and artists in the tumultuous century between the 1860s and the 1960s.